PENGARUH MODEL CONTEXTUAL TEACHING AND LEARNING TERHADAP HASIL BELAJAR IPS SISWA SEKOLAH DASAR: SYSTEMATIC LITERATURE REVIEW - Dewi Yanti; Repa Fajriyani S; Karismayanti Diana Putri; Yuyun Dwi Haryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
The low learning outcomes of Social Studies (Ilmu Pengetahuan Sosial/IPS) among elementary school students remain a common problem in the learning process. This condition is largely caused by the use of conventional learning models that do not sufficiently relate learning materials to students’ real-life contexts. The Contextual Teaching and Learning (CTL) model is considered a potential solution because it emphasizes the connection between learning content and students’ everyday experiences. This study aims to systematically analyze the effect of the CTL model on Social Studies learning outcomes of elementary school students through a Systematic Literature Review (SLR) approach. The research method employed was SLR by reviewing scientific articles obtained from Google Scholar, Garuda, and DOAJ databases published between 2020 and 2025. The articles were selected based on predetermined inclusion and exclusion criteria, resulting in a number of relevant studies for analysis. The data analysis techniques used were content analysis and thematic synthesis of the research findings. The results of the review indicate that the consistent implementation of the CTL model has a positive effect on improving Social Studies learning outcomes of elementary school students, including cognitive, affective, and learning engagement aspects. CTL enhances students’ conceptual understanding, learning motivation, and critical thinking skills through meaningful and contextual learning experiences. Therefore, the CTL model is recommended as an effective alternative learning model to improve the quality of Social Studies instruction in elementary schools.